The organizational ecosystem change model for sustainability and justice - Kaul, Mokshda; Oonk, David; Darnall, Nicole; Karwat, Darshan M. A. (Frontiers in Sustainability, 2025)
Addressing complex societal challenges like sustainability and justice requires significant coordinated action within and across organizations. But existing theories for understanding organizational change generally focus on change within a single organization. This perspective misses important interconnectivity and dependencies that organizations have with other entities that both facilitate and impede organizational change. We explore these critical interconnectivities and dependencies and propose an Organizational Ecosystem Change Model (OECM) that considers how organizational change occurs within an ecosystem of organizations. We illustrate the relevance of this model by applying it to an organization’s attempt to change in response to complex sustainability challenges that require the federal ecosystem of organizations to incorporate energy and environmental justice values into their work. Through interviews and analyzing official agency documents and internal archival documents with OECM, we demonstrate that organization change is (1) affected by the nature of hierarchy within the ecosystem, (2) requires significant coordination across the ecosystem, and (3) warrants codifying new organizational norms and processes that can create ecosystem-wide support for change. OECM model and our empirical application advance our understanding of organizational change theory and offer practical insights for organizational ecosystems dealing with similar change-related tasks to address complex sustainability challenges.